"There Is No Substitute for a Sense of Reality": Humanizing the Humanities. Issue 6 (December 2015) - Laverty, Megan J.
Abstract: Do the humanities have a future? In the face of an increased emphasis on the so‐called practical applicability of education, some educators worry that the presence of humanistic study in schools and universities is gravely threatened. In the short‐term, scholars have rallied to defend the humanities by demonstrating how they do, in fact, advance our practical interests. Martha Nussbaum, for example, argues that the humanities uniquely support democratic citizenship by cultivating critical thinking and narrative imagination — two skills needed for the development of sympathetic and autonomous judgment. Defending the humanities in this manner, however, puts practitioners of the humanities in an impossible position. In this essay, Megan Laverty explains that while arguments such as Nussbaum's, which defend the instrumental value of the humanities, are persuasive and strategic, their use is double‐edged. They belie the fact that the humanities are valuable for their own sake. Such arguments imply that the humanities derive their value from their ability to provide extrinsic benefits such as critical thinking and narrative imagination. Moreover, they can prevent individuals from discovering that the value of the humanities is revealed over time and from the inside out. In fact, having to answer the question of why the humanities matter puts us in an impossible position precisely because humanistic study is what Laverty describes, drawing upon the work of Talbot Brewer and R. F. Holland, as a form of dialectical activity: one in which the activity's constitutive ideals and internal goods are progressively clarified by means of the individual's ongoing engagement in the activity itself. Having redescribed the humanities as intrinsically valuable, Laverty goes on to distinguish humanistic study from other forms of dialectical activity, arguing that the humanities call upon students to imagine alternative linguistic and conceptual possibilities — thereby connecting us with others. It is in the pursuit of this question about the nature of our humanity — not its answer, but the question itself — that the meaning of humanistic study continues, indefinitely, to unfold.